Novel high-strength plastic magnesium alloy and preparation and processing method thereof
By adopting specific components and preparation and processing methods in magnesium alloys, the problem of inequality in plastic deformation capabilities and the formation of LPSO structural phases is solved, and a high-strength and high-plastic magnesium alloys are realized, which meets the aerospace Strict requirements in other fields.
Patent Information
- Application Number
- CN202411683600.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-11
AI Technical Summary
Magnesium alloys have shortcomings in plastic deformation capabilities, and the formation of LPSO structural phases is uneven, which affects the quality and performance of the alloy.
The composition of high-strength plastic magnesium alloy is composed of Gd 3~10%, Y 1~5%, Sn 0.3~5.0%, Sb 0.3~1.5%, Ge 0.3~1.0%, Ca 0.3~1.0%, Sr 0.3~1.2 % and Zr 0.3~1.0%, and control the controllability of alloy structure through specific preparation and processing methods, including multi-stage heating, mechanical stirring, filtration, casting, heat treatment and aging treatment.
It improves the strength and plasticity of magnesium alloys, enhances the controllability of the structure, reduces the use of rare earth elements, reduces production costs and energy consumption, and meets the strict requirements for material performance in the fields of aerospace and other fields.
Abstract
Description
Technical Field
[0001] The invention relates to a novel high-strength plastic magnesium alloy and a preparation and processing method thereof, belonging to the field of industrial magnesium alloys. Background Art
[0002] As the lightest metal structural material currently, magnesium alloy has become an important candidate material for achieving lightweight goals in aerospace, weapons and equipment and other fields. Existing studies have fully confirmed that the comprehensive performance of deformed magnesium alloys is much higher than that of cast magnesium alloys. However, magnesium alloys have a close-packed hexagonal structure and only have three independent slip systems at room temperature, so they can only be effectively deformed under high temperature conditions. The development of new high-strength plastic deformation magnesium alloys is particularly important and urgent, which has become a key direction for research and development in related fields. The successful development and application of new high-strength plastic deformation magnesium alloys is expected to break through the application limitations of existing magnesium alloys, expand the flexibility and convenience of their processing and manufacturing, reduce production energy consumption and costs, better meet the stringent requirements of aerospace, weapons and equipment for material performance, and ensure the safety and reliability of equipment.
[0003] In order to effectively improve the strength and plasticity of magnesium alloys, the current research focuses on adding Zn elements to rare earth magnesium alloys to promote the formation of long-period structural phases (i.e., LPSO structural phases). The LPSO structural phase is generally believed to have the ability to simultaneously enhance the strength and plasticity of the alloy. As for the formation mechanism of the LPSO structural phase, it mainly depends on the mutual binding between Zn atoms and rare earth atoms. Its specific formation process is not only subject to strict limitations on composition, but also depends on external conditions such as specific temperature. It can be seen that solidification conditions play a decisive role in whether the phase can be successfully formed. However, a lot of practical experience shows that the LPSO structural phase exhibits obvious inhomogeneous characteristics during the formation process. Especially in the case of large-scale magnesium alloy ingots, the heat-resistant properties of rare earth elements themselves greatly prolong the solidification time of the ingot. In this process, the formation of the LPSO structural phase will produce a transitional structure according to the change of the temperature gradient, and the formation of this structure is extremely difficult to control. In the subsequent deformation process of the magnesium alloy, the transitional structure is very easy to evolve into a crack source, which in turn has an adverse effect on the quality and performance of the magnesium alloy. In addition, due to the existence of the LPSO structural phase, a large number of rare earth atoms will be occupied, which will weaken the precipitation strengthening ability of the alloy to a certain extent.
[0004] In order to give full play to the strength characteristics of rare earth magnesium alloys, more elements have to be introduced. The original lightweight characteristics of magnesium alloys have been significantly weakened, which to a certain extent affects the application prospects of magnesium alloys in certain fields with high lightweight requirements. Summary of the invention
[0005] Based on the above prior art, the purpose of the present invention is to provide a new type of high-strength plastic magnesium alloy, which effectively makes up for the shortcomings of magnesium alloy in terms of plastic deformation ability.
[0006] Another object of the present invention is to provide a method for preparing and processing the novel high-strength and high-plastic magnesium alloy, in order to achieve the controllability of the magnesium alloy structure and further expand the application scope of the magnesium alloy.
[0007] To achieve the above object, the present invention adopts the following technical solutions: A high-strength and plastic magnesium alloy comprises, by mass percentage, 3-10% Gd, 1-5% Y, 0.3-5.0% Sn, 0.3-1.5% Sb, 0.3-1.0% Ge, 0.3-1.0% Ca, 0.3-1.0% Sr, 0.3-1.2% Zr, and the remainder is pure magnesium.
[0008] Preferably, in the high-strength and plastic magnesium alloy, the following conditions are satisfied: Sb+Ge≤2.0%, Ca+Sr≤1.0%.
[0009] A method for preparing the high-strength and plastic magnesium alloy comprises the following steps: (1) Prepare raw materials according to the target alloy composition, melt part of the pure magnesium, and control the melt temperature between 700℃ and 720℃; (2) Add Gd and Y elements, raise the temperature to 780-800°C, add Sb and Ge elements, and keep the temperature for 5-10 minutes; continue to raise the temperature to 800-820°C, and after the metal is completely melted, add Mg-Zr master alloy, stir mechanically, and keep the temperature for 10-30 minutes under this condition, then introduce argon gas into the melt and keep it for 5-10 minutes; (3) Start cooling down and add the remaining pure magnesium at the same time. When the temperature drops to 780°C~800°C, add metal Sn, and then continue cooling down. When the temperature drops to 750°C, add Mg-Ca and Mg-Sr master alloys. When the temperature drops to 700~720°C, stop stirring and filter. (4) pouring the filtered magnesium alloy melt to form an ingot; (5) After demolding the ingot, heat it to 400-420°C and keep it for 1-2 hours, then heat it to 510-530°C and keep it for 2-3 hours; (6) The heated ingot is taken out and deformed and opened, and then the deformed billet is quickly air-cooled until the surface temperature drops to 300°C~350°C; (7) The billet after cooling treatment is subjected to induction heating, and after reaching 510-530°C, it is kept at this temperature for 5-36 hours to complete the homogenization heat treatment; (8) The homogenized alloy is directly subjected to hot working, and after deformation, it is rapidly water-cooled to form a supersaturated solid solution; (9) The deformed material is artificially aged under the combined action of pulse current + DC current, the aging temperature is controlled between 120~250℃, the total aging time is controlled within 100 hours, and then air-cooled; (10) Place the aged material in a tank filled with liquid nitrogen for 2 to 3 hours, then add room temperature water to the tank until it is completely filled, and place the tank in a freezer at -20°C to -10°C for 2 to 6 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0010] In step (1), 30% of the total amount of pure magnesium is preheated and placed in a medium frequency induction furnace. After all of it is melted, the remaining 90% of the pure magnesium is added and heated continuously until all of it is melted. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0011] During the alloy smelting process, pure metals are used for Mg, Gd, Y, Sn, Sb and Ge, Mg-10%Ca and Mg-10%Sr master alloys are used for Ca and Sr, and Mg-30%Zr master alloy is used for Zr.
[0012] In step (4), the ingot casting mold is preheated at a temperature of 450-500°C. After the magnesium alloy melt is completely solidified, the ingot casting mold is cooled by one or a combination of air cooling, water mist cooling, hot water cooling and room temperature water cooling.
[0013] In step (6), the blanking method includes forging, extrusion or forging followed by extrusion, wherein the total forging deformation is controlled within a range of 10-20%, and the extrusion ratio is controlled within a range of 4-6.
[0014] In step (8), the processing method includes one or a combination of forging, extrusion, and rolling.
[0015] In step (9), the artificial aging is single-stage aging or multi-stage aging.
[0016] In step (10), when room temperature water is added, the water flow rate is gradually reduced from 10 L / min to 1 L / min.
[0017] Beneficial effects of the present invention: 1. From the perspective of alloy design, we avoid using elements such as Zn that may form an uncontrollable LPSO structural phase, and instead use Sn, Sb and Ge elements that can promote the activation of the slip system, thereby improving the controllability of the structure. In addition, the addition of Ca elements to the alloy can not only form a high-temperature stable phase, but also reduce the density of the alloy, compensating to a certain extent for the negative effects of rare earth elements.
[0018] 2. Adding rare earth elements, Ge and Sb to prevent the melt from oxidation during the heating process, and adding easily fusible and oxidizable elements such as Sn, Ca and Sr during the cooling process can effectively improve the quality of the ingot.
[0019] 3. Placing the alloy homogenization heat treatment step after the billet is opened can effectively improve the diffusion capacity of high solid solubility elements, especially Sn elements. If high-temperature homogenization is performed directly, oxidation and overburning problems may occur.
[0020] 4. The combined action of pulsating current + direct current for aging can effectively stimulate element enrichment and nucleation, which has a positive effect on improving the nucleation efficiency of the strengthening phase.
[0021] 5. In the later stage, in addition to using liquid nitrogen, cold water pouring and freezing were also used to reduce the deformation residual stress of the material, further improving the stability of the organization. DETAILED DESCRIPTION
[0022] The present invention is further described below in conjunction with the embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.
[0023] The high-strength plastic magnesium alloy provided by the present invention comprises the following components by mass percentage: Gd 3-10%, Y 1-5%, Sn 0.3-5.0%, Sb 0.3-1.5%, Ge 0.3-1.0%, Ca 0.3-1.0%, Sr 0.3-1.2%, Zr0.3-1.0%, and the rest is pure magnesium.
[0024] Preferably, based on the deformation capabilities of Sb and Ge and the low solid solubility characteristics of the four elements in magnesium, in the high-strength and plastic magnesium alloy, the following conditions are satisfied: Sb+Ge≤2.0%, Ca+Sr≤1.0%.
[0025] The preparation and processing method of the high-strength plastic magnesium alloy of the present invention specifically comprises the following steps: (1) Prepare the raw materials according to the target alloy composition and dry them at 150-200°C. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. Control the melt temperature between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane with a gas flow rate ratio of 20:1.
[0026] (2) Add Gd and Y elements, then increase the power. When the temperature rises to 780-800°C, add Sb and Ge elements and keep warm for 5-10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 10-30 minutes, then introduce argon into the melt and keep it for 5-10 minutes.
[0027] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add metal Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0028] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at a temperature of 450-500°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled by air cooling, water mist cooling, hot water cooling, and room temperature water cooling.
[0029] (5) After demolding the ingot, place it in a heat treatment furnace for heating, raise the temperature to 400~420℃ and keep it at this temperature for 1~2 hours, then heat it to 510~530℃ and keep it at this temperature for 2~3 hours.
[0030] (6) The heated ingot is taken out and deformed and blanked. The blanking methods include forging, extrusion or forging followed by extrusion. The total forging deformation is controlled within 10-20%, and the extrusion ratio is controlled within the range of 4-6. The deformed blank is rapidly air-cooled until the surface temperature drops to 300°C-350°C.
[0031] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature to 510-530°C and then maintained at that temperature for 5-36 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the elements.
[0032] (8) The homogenized alloy is directly subjected to hot processing, which includes one or a combination of forging, extrusion, and rolling. After deformation, it is quickly water-cooled to form a supersaturated solid solution.
[0033] (9) The deformed material is artificially aged under the combined action of pulse current + direct current. The aging temperature is controlled between 120 and 250 °C, and the total aging time is controlled within 100 hours. It can be single-stage aging or multi-stage aging, followed by air cooling.
[0034] (10) Place the aged material in a liquid nitrogen tank for 2 to 3 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 2 to 6 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0035] In addition, it should be noted that the term "high strength and plasticity" in the present invention refers to the magnesium alloy having high strength and high plasticity. However, there is no specific limitation on the strength and plasticity of the magnesium alloy, which is related to the total amount of elements. The higher the total amount, the higher the strength and the lower the plasticity. For example, most of the following embodiments are above 400 and the elongation is greater than 5%. However, for Example 5, although the strength is only 340MPa, the total amount of elements is very low, so it also belongs to high strength.
[0036] Example 1 The alloy design composition is Mg-8Gd-4Y-2Sn-1Sb-1Ge-0.5Ca-0.5Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0037] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0038] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0039] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 480°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0040] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 2 hours.
[0041] (6) The heated ingot is taken out and subjected to multi-directional forging to open the blank, with the total deformation controlled at 20%. The forged blank is rapidly air-cooled until the surface temperature drops to 350°C.
[0042] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 30 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0043] (8) The homogenized alloy is hot extruded with an extrusion ratio of 8 and online quenched at the exit of the extruder to form a supersaturated solid solution.
[0044] (9) The extruded material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 64 hours, and then air cooling is performed.
[0045] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0046] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 470MPa, the average yield strength is 360MPa, and the elongation is 9.0%.
[0047] Example 2 The alloy design composition is Mg-10Gd-5Y-2Sn-1Sb-1Ge-0.7Ca-0.3Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0048] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0049] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0050] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 480°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0051] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 2 hours.
[0052] (6) The heated ingot is taken out and subjected to multi-directional forging to open the blank, with the total deformation controlled at 20%. The forged blank is rapidly air-cooled until the surface temperature drops to 350°C.
[0053] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 30 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0054] (8) The homogenized alloy is hot extruded with an extrusion ratio of 8 and online quenched at the exit of the extruder to form a supersaturated solid solution.
[0055] (9) The extruded material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 60 hours, and then air cooling is performed.
[0056] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0057] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 483MPa, the average yield strength is 370MPa, and the elongation is 9.5%.
[0058] Example 3 The alloy design composition is Mg-7Gd-3Y-1.5Sn-0.5Sb-0.5Ge-0.3Ca-0.7Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0059] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0060] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0061] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 460°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0062] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 2 hours.
[0063] (6) The heated ingot is taken out and extruded into a blank with an extrusion ratio of 5. The extruded blank is rapidly air-cooled until the surface temperature drops to 350°C.
[0064] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 24 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0065] (8) The homogenized alloy is subjected to multi-directional forging with a single pass pressure of 45% for a total of 6 passes. After forging, it is quickly water-cooled to form a supersaturated solid solution.
[0066] (9) The forged material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 40 hours, and then air cooling is performed.
[0067] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0068] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the sample, and take the average value of the test results of the sample. After testing, the average tensile strength of the sample is 465MPa, the average yield strength is 335MPa, and the elongation is 10.5%.
[0069] Example 4 The alloy design composition is Mg-9Gd-4Y-3Sn-0.5Sb-0.5Ge-0.7Ca-0.3Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0070] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0071] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0072] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 460°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0073] (5) After demolding the ingot, place it in a heat treatment furnace for heating, raise the temperature to 400°C and keep it at this temperature for 2 hours, then heat it to 510°C and keep it at this temperature for 2 hours.
[0074] (6) The heated ingot is taken out and extruded into a blank with an extrusion ratio of 4. The blank after extrusion is rapidly air-cooled until the surface temperature drops to 330°C.
[0075] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 510°C, the temperature is maintained for 20 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0076] (8) The homogenized alloy is subjected to multi-directional forging with a single pass pressure of 45% for a total of 6 passes. After forging, it is quickly water-cooled to form a supersaturated solid solution.
[0077] (9) The forged material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 24 hours, and then air cooling is performed.
[0078] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0079] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 486MPa, the average yield strength is 363MPa, and the elongation is 10.5%.
[0080] Example 5 The alloy design composition is Mg-3Gd-1Y-0.5Sr-0.5Sb-0.5Ge-0.5Ca-0.5Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0081] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0082] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0083] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 460°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0084] (5) After demolding the ingot, place it in a heat treatment furnace for heating, raise the temperature to 400°C and keep it at that temperature for 2 hours, then heat it to 520°C and keep it at that temperature for 2 hours.
[0085] (6) The heated ingot is taken out and subjected to multi-directional forging to open the blank, with the total deformation controlled at 20%. The extruded blank is rapidly air-cooled until the surface temperature drops to 330°C.
[0086] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 24 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0087] (8) The homogenized alloy was subjected to multi-directional forging with a single pass pressing amount of 45% for a total of 6 passes. After forging, the alloy was returned to the furnace for 2 hours and then hot extruded with an extrusion ratio of 23. Online quenching was performed at the exit of the extruder to form a supersaturated solid solution.
[0088] (9) The extruded material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 36 hours, and then air cooling is performed.
[0089] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0090] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 340MPa, the average yield strength is 267MPa, and the elongation is 16.5%.
[0091] Example 6 The alloy design composition is Mg-6Gd-3Y-2.5Sn-1Sb-0.5Ge-0.7Ca-0.3Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0092] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0093] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0094] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 480°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0095] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 2 hours.
[0096] (6) The heated ingot is taken out and subjected to multi-directional forging to open the blank, with the total deformation controlled at 15%. The forged blank is rapidly air-cooled until the surface temperature drops to 350°C.
[0097] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is maintained for 18 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0098] (8) The homogenized alloy is hot extruded with an extrusion ratio of 8 and online quenched at the exit of the extruder to form a supersaturated solid solution.
[0099] (9) The extruded material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 36 hours, and then air cooling is performed.
[0100] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0101] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 410MPa, the average yield strength is 315MPa, and the elongation is 13.5%.
[0102] Example 7 The alloy design composition is Mg-5Gd-2Y-1.5Sn-0.5Sb-0.5Ge-0.7Ca-0.3Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0103] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0104] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0105] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 480°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0106] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 3 hours.
[0107] (6) The heated ingot is taken out and subjected to multi-directional forging to open the blank, with the total deformation controlled at 20%. The forged blank is rapidly air-cooled until the surface temperature drops to 350°C.
[0108] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is maintained for 18 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0109] (8) The homogenized alloy is hot extruded with an extrusion ratio of 15, and then the extruded sheet is hot rolled in a single pass. After rolling, it is quickly water-cooled to form a supersaturated solid solution.
[0110] (9) The rolled material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 60 hours, and then air cooling is performed.
[0111] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 5 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0112] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 365MPa, the average yield strength is 297MPa, and the elongation is 14.0%.
[0113] Example 8 The alloy design composition is Mg-9Gd-4Y-2Sn-1Sb-1Ge-0.5Ca-0.3Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0114] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0115] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0116] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 460°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0117] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 3 hours.
[0118] (6) The heated ingot is taken out and extruded into a blank with an extrusion ratio of 4. The blank after extrusion is rapidly air-cooled until the surface temperature drops to 340°C.
[0119] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 24 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0120] (8) The homogenized alloy was subjected to multi-directional forging with a single pass pressing amount of 45% for a total of 6 passes. The forged plate was then hot extruded with an extrusion ratio of 23 and quenched online at the extruder outlet to form a supersaturated solid solution.
[0121] (9) The rolled material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 48 hours, and then air cooling is performed.
[0122] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 5 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0123] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 490MPa, the average yield strength is 390MPa, and the elongation is 8.5%.
[0124] Example 9 The alloy design composition is Mg-5Gd-2Y-5Sn-1Sb-1Ge-0.7Ca-0.3Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0125] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0126] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0127] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 480°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0128] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 2 hours.
[0129] (6) The heated ingot is taken out and extruded into a blank with an extrusion ratio of 6. The extruded blank is rapidly air-cooled until the surface temperature drops to 330°C.
[0130] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 24 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0131] (8) The homogenized alloy is rolled in multiple passes and rapidly water-cooled after rolling to form a supersaturated solid solution.
[0132] (9) The rolled material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 200°C, the aging time is 28 hours, and then air cooling is performed.
[0133] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0134] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the sample, and take the average value of the test results of the sample. After testing, the average tensile strength of the sample is 357MPa, the average yield strength is 299MPa, and the elongation is 13.5%.
[0135] Example 10 The alloy design composition is Mg-8Gd-4Y-3Sn-0.5Sb-0.5Ge-0.5Ca-0.5Sr-0.5Zr (wt.%), using pure magnesium (purity>99%), pure Gd (purity>99.9%), pure Y (purity>99.9%), pure Sn (purity>99.9%), pure Sb (purity>99.9%), pure Ge (purity>99.9%), Mg-10%Ca, Mg-10%Sr and Mg-30%Zr master alloy as raw materials. The preparation and processing steps of the alloy are as follows: (1) Dry the raw materials at 180°C for 2 hours. Preheat 30% of the pure magnesium and place it in a medium frequency induction furnace. After it is completely melted, add 90% of the remaining pure magnesium and continue heating until it is completely melted. The melt temperature is controlled between 700°C and 720°C. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:1.
[0136] (2) Add pure Gd and pure Y, then increase the power. When the temperature rises to 780-800°C, add pure Sb and pure Ge, and keep warm for 10 minutes. Continue to increase the power and raise the temperature to above 800°C. Control the temperature not to exceed 820°C. After the elements are completely melted, add Mg-30%Zr master alloy and perform mechanical stirring to accelerate the dispersion of the elements. Keep warm under this condition for 20 minutes, then introduce argon into the melt and keep it for 10 minutes.
[0137] (3) After completing the above steps, reduce the power of the induction furnace, start cooling, and add the remaining pure magnesium at the same time. When the temperature drops to 780℃~800℃, add pure Sn, and then continue to cool down. When the temperature drops to 750℃, add Mg-10%Ca and Mg-10%Sr intermediate alloys. When the temperature drops to 700~720℃, stop stirring and use MgO ceramic sheets for filtering.
[0138] (4) The filtered magnesium alloy melt is poured, and the ingot mold is preheated at 480°C. After the magnesium alloy melt is completely solidified, the ingot mold is cooled in three stages, namely, water mist cooling, hot water cooling, and room temperature water cooling.
[0139] (5) After demolding the ingot, place it in a heat treatment furnace for heating. Raise the temperature to 420°C and keep it at that temperature for 2 hours. Then heat it to 520°C and keep it at that temperature for 2 hours.
[0140] (6) The heated ingot is taken out and extruded into a blank with an extrusion ratio of 4. The extruded blank is rapidly air-cooled until the surface temperature drops to 350°C.
[0141] (7) The billet that has been cooled is subjected to induction heating to rapidly increase the temperature. After reaching 520°C, the temperature is kept for 30 hours to complete the entire homogenization heat treatment and achieve uniform diffusion of the alloy elements.
[0142] (8) The homogenized alloy is extruded with an extrusion ratio of 8, followed by single-pass rolling. After rolling, the alloy is rapidly water-cooled to form a supersaturated solid solution.
[0143] (9) The rolled material is artificially aged under the combined action of pulse current + direct current, the aging temperature is 220°C, the aging time is 24 hours, and then air cooling is performed.
[0144] (10) Place the aged material in a liquid nitrogen tank for 2 hours, then add room temperature water into the tank and gradually reduce the water flow rate from 10 L / min to 1 L / min, measured by the overall volume of the liquid nitrogen tank until it is completely filled, and place the tank body into a freezer and keep it at -20℃~-10℃ for 4 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
[0145] Take 3 tensile specimens from the head, middle and tail of the sample. Refer to GB / T 228.1 to test the tensile strength, yield strength and elongation of the specimens, and take the average value of the test results of the specimens. After testing, the average tensile strength of the sample is 488MPa, the average yield strength is 320MPa, and the elongation is 10.5%.
Claims
1. A high-strength plastic magnesium alloy, characterized in that: The magnesium alloy has the following components in percentage by mass: Gd 3-10%, Y 1-5%, Sn 0.3-5.0%, Sb 0.3-1.5%, Ge 0.3-1.0%, Ca 0.3-1.0%, Sr 0.3-1.2%, Zr 0.3-1.0%, and the rest is pure magnesium.
2. The high-strength and plastic magnesium alloy according to claim 1, characterized in that: In the high-strength and plastic magnesium alloy, the following conditions are satisfied: Sb+Ge≤2.0%, Ca+Sr≤1.0%.
3. A method for preparing the high-strength and plastic magnesium alloy according to claim 1 or 2, characterized in that: The steps include: (1) Prepare raw materials according to the target alloy composition, melt part of the pure magnesium, and control the melt temperature between 700℃ and 720℃; (2) Add Gd and Y elements, raise the temperature to 780-800°C, then add Sb and Ge elements, and keep the temperature for 5-10 minutes; continue to raise the temperature to 800-820°C, and after the metal is completely melted, add Mg-Zr master alloy, stir mechanically, and keep the temperature for 10-30 minutes under this condition, then introduce argon gas into the melt and keep it for 5-10 minutes; (3) Start cooling down and add the remaining pure magnesium at the same time. When the temperature drops to 780°C~800°C, add metal Sn, and then continue cooling down. When the temperature drops to 750°C, add Mg-Ca and Mg-Sr master alloys. When the temperature drops to 700~720°C, stop stirring and filter. (4) pouring the filtered magnesium alloy melt to form an ingot; (5) After demolding the ingot, heat it to 400-420°C and keep it for 1-2 hours, then heat it to 510-530°C and keep it for 2-3 hours; (6) The heated ingot is taken out and deformed and opened, and then the deformed billet is quickly air-cooled until the surface temperature drops to 300°C~350°C; (7) The billet after cooling treatment is subjected to induction heating, and after reaching 510-530°C, it is kept at this temperature for 5-36 hours to complete the homogenization heat treatment; (8) The homogenized alloy is directly subjected to hot working, and after deformation, it is rapidly water-cooled to form a supersaturated solid solution; (9) The deformed material is artificially aged under the combined action of pulse current + DC current, the aging temperature is controlled between 120~250℃, the total aging time is controlled within 100 hours, and then air-cooled; (10) Place the aged material in a tank filled with liquid nitrogen for 2 to 3 hours, then add room temperature water to the tank until it is completely filled, and place the tank in a freezer at -20°C to -10°C for 2 to 6 hours, then slowly heat it to room temperature, take out the sample and dry it to remove water.
4. The method for preparing a high-strength plastic magnesium alloy according to claim 3, characterized in that: In step (1), 30% of the total amount of pure magnesium is preheated and placed in a medium frequency induction furnace. After all of it is melted, the remaining 90% of the pure magnesium is added and heated continuously until all of it is melted. The melting process is protected by a mixed gas of argon and tetrafluoroethane, and the gas flow rate ratio is 20:
1.
5. The method for preparing a high-strength and plastic magnesium alloy according to claim 3, characterized in that: During the alloy smelting process, pure metals are used for Mg, Gd, Y, Sn, Sb and Ge, Mg-10%Ca and Mg-10%Sr master alloys are used for Ca and Sr, and Mg-30%Zr master alloy is used for Zr.
6. The method for preparing a high-strength and plastic magnesium alloy according to claim 3, characterized in that: In step (4), the ingot casting mold is preheated at a temperature of 450-500°C. After the magnesium alloy melt is completely solidified, the ingot casting mold is cooled by one or a combination of air cooling, water mist cooling, hot water cooling and room temperature water cooling.
7. The method for preparing a high-strength and plastic magnesium alloy according to claim 3, characterized in that: In step (6), the blanking method includes forging, extrusion or forging followed by extrusion, wherein the total forging deformation is controlled within a range of 10-20%, and the extrusion ratio is controlled within a range of 4-6.
8. The method for preparing a high-strength and plastic magnesium alloy according to claim 3, characterized in that: In step (8), the processing method includes one or a combination of forging, extrusion, and rolling.
9. The method for preparing a high-strength and plastic magnesium alloy according to claim 3, characterized in that: In step (9), the artificial aging is single-stage aging or multi-stage aging.
10. The method for preparing a high-strength and plastic magnesium alloy according to claim 3, characterized in that: In step (10), when room temperature water is added, the water flow rate is gradually reduced from 10 L / min to 1 L / min.
Citation Information
Cited By
Magnesium alloy plate and temperature-controlled hot rolling preparation method thereof
CN120055067A
Method suitable for reducing residual stress of magnesium alloy plate
CN122235800A